Fate and transformation of silver nanoparticles in different biological conditions - Pem, Barbara; Ćurlin, Marija; Domazet Jurašin, Darija; Vrček, Valerije; Barbir, Rinea; Micek, Vedran; Fratila, Raluca M.; de la Fuente, Jesus M.; Vinković Vrček, Ivana (Beilstein Journal of Nanotechnology, 2021)
The exploitation of silver nanoparticles (AgNPs) in biomedicine represents more than one third of their overall application. Despite their wide use and significant amount of scientific data on their effects on biological systems, detailed insight into their in vivo fate is still lacking. This study aimed to elucidate the biotransformation patterns of AgNPs following oral administration. Colloidal stability, biochemical transformation, dissolution, and degradation behaviour of different types of AgNPs were evaluated in systems modelled to represent biological environments relevant for oral administration, as well as in cell culture media and tissue compartments obtained from animal models. A multimethod approach was employed by implementing light scattering (dynamic and electrophoretic) techniques, spectroscopy (UV–vis, atomic absorption, nuclear magnetic resonance) and transmission electron microscopy. The obtained results demonstrated that AgNPs may transform very quickly during their journey through different biological conditions. They are able to degrade to an ionic form and again reconstruct to a nanoparticulate form, depending on the biological environment determined by specific body compartments. As suggested for other inorganic nanoparticles by other research groups, AgNPs fail to preserve their specific integrity in in vivo settings.
Keywords: animal tissue; biological media; nanoparticle aggregation; nanoparticle dissolution; nanoparticle reformation; silver nanoparticles

(untitled) - Syafiuddin, A.; Salmiati; Salim, M. R.; Beng Hong Kueh, A.; Hadibarata, T.; Nur, H. (J. Chin. Chem. Soc., 2017)

(untitled) - Haider, A.; Kang, I.-K. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Burdușel, A.-C.; Gherasim, O.; Grumezescu, A. M.; Mogoantă, L.; Ficai, A.; Andronescu, E. (Nanomaterials, 2018)

Nanotechnology in Food

(untitled) - Akter, M.; Sikder, M. T.; Rahman, M. M.; Ullah, A. K. M. A.; Hossain, K. F. B.; Banik, S.; Hosokawa, T.; Saito, T.; Kurasaki, M. (J. Adv. Res., 2018)

(untitled) - Jurašin, D. D.; Ćurlin, M.; Capjak, I.; Crnković, T.; Lovrić, M.; Babič, M.; Horák, D.; Vinković Vrček, I.; Gajović, S. (Beilstein J. Nanotechnol., 2016)

(untitled) - Marchioni, M.; Jouneau, P.-H.; Chevallet, M.; Michaud-Soret, I.; Deniaud, A. (Coord. Chem. Rev., 2018)

(untitled) - Axson, J. L.; Stark, D. I.; Bondy, A. L.; Capracotta, S. S.; Maynard, A. D.; Philbert, M. A.; Bergin, I. L.; Ault, A. P. (J. Phys. Chem. C, 2015)

(untitled) - Feliu, N.; Docter, D.; Heine, M.; Del Pino, P.; Ashraf, S.; Kolosnjaj-Tabi, J.; Macchiarini, P.; Nielsen, P.; Alloyeau, D.; Gazeau, F.; Stauber, R. H.; Parak, W. J. (Chem. Soc. Rev., 2016)

(untitled) - Sharma, V. K.; Siskova, K. M.; Zboril, R.; Gardea-Torresdey, J. L. (Adv. Colloid Interface Sci., 2014)

(untitled) - Fröhlich, E.; Roblegg, E. (Arch. Toxicol., 2016)

(untitled) - Muraleetharan, V.; Mantaj, J.; Swedrowska, M.; Vllasaliu, D. (RSC Adv., 2019)

(untitled) - Liu, J.; Wang, Z.; Liu, F. D.; Kane, A. B.; Hurt, R. H. (ACS Nano, 2012)

(untitled) - Aaseth, J.; Olsen, A.; Halse, J.; Hovig, T. (Scand. J. Clin. Lab. Invest., 1981)

(untitled) - Fisher, N. M.; Marsh, E.; Lazova, R. (J. Am. Acad. Dermatol., 2003)

(untitled) - White, J. M. L.; Powell, A. M.; Brady, K.; Russell-Jones, R. (Clin. Exp. Dermatol., 2003)

(untitled) - Tomi, N. S.; Kränke, B.; Aberer, W. (Lancet, 2004)

(untitled) - Kim, Y.; Suh, H. S.; Cha, H. J.; Kim, S. H.; Jeong, K. S.; Kim, D. H. (Am. J. Ind. Med., 2009)

(untitled) - Jonas, L.; Bloch, C.; Zimmermann, R.; Stadie, V.; Gross, G. E.; Schäd, S. G. (Ultrastruct. Pathol., 2007)

(untitled) - Chevallet, M.; Veronesi, G.; Fuchs, A.; Mintz, E.; Michaud-Soret, I.; Deniaud, A. (Biochim. Biophys. Acta, Gen. Subj., 2017)

(untitled) - Peloquin, D. M.; Baumann, E. J., Jr; Luxton, T. P. (Chemosphere, 2020)

(untitled) - Loza, K.; Diendorf, J.; Sengstock, C.; Ruiz-Gonzalez, L.; Gonzalez-Calbet, J. M.; Vallet-Regi, M.; Köller, M.; Epple, M. (J. Mater. Chem. B, 2014)

(untitled) - Liu, J.; Sonshine, D. A.; Shervani, S.; Hurt, R. H. (ACS Nano, 2010)

(untitled) - Danscher, G.; Locht, L. J. (Histochem. Cell Biol., 2010)

(untitled) - Wu, W.; Zhang, R.; McClements, D. J.; Chefetz, B.; Polubesova, T.; Xing, B. (Environ. Sci. Technol., 2018)

(untitled) - Geng, H.; Poologasundarampillai, G.; Todd, N.; Devlin-Mullin, A.; Moore, K. L.; Golrokhi, Z.; Gilchrist, J. B.; Jones, E.; Potter, R. J.; Sutcliffe, C.; O'Brien, M.; Hukins, D. W. L.; et al. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Du, T.; Shi, G.; Liu, F.; Zhang, T.; Chen, W. (Environ. Sci. Technol., 2019)

(untitled) - Martinolich, A. J.; Park, G.; Nakamoto, M. Y.; Gate, R. E.; Wheeler, K. E. (Environ. Sci. Technol., 2012)

(untitled) - Ngamchuea, K.; Batchelor-McAuley, C.; Compton, R. G. (Nanotoxicology, 2018)

(untitled) - Teubl, B. J.; Stojkovic, B.; Docter, D.; Pritz, E.; Leitinger, G.; Poberaj, I.; Prassl, R.; Stauber, R. H.; Fröhlich, E.; Khinast, J. G.; Roblegg, E. (Clin. Oral Invest., 2018)

Intracellular Delivery II. Fundamental Biomedical Technologies - Fröhlich, E.; Roblegg, E. (Mucus as Physiological Barrier to Intracellular Delivery, 2014)

(untitled) - Walczak, A. P.; Fokkink, R.; Peters, R.; Tromp, P.; Herrera Rivera, Z. E.; Rietjens, I. M. C. M.; Hendriksen, P. J. M.; Bouwmeester, H. (Nanotoxicology, 2012)

(untitled) - Bove, P.; Malvindi, M. A.; Kote, S. S.; Bertorelli, R.; Summa, M.; Sabella, S. (Nanoscale, 2017)

(untitled) - Boudreau, M. D.; Imam, M. S.; Paredes, A. M.; Bryant, M. S.; Cunningham, C. K.; Felton, R. P.; Jones, M. Y.; Davis, K. J.; Olson, G. R. (Toxicol. Sci., 2016)

(untitled) - Loeschner, K.; Hadrup, N.; Qvortrup, K.; Larsen, A.; Gao, X.; Vogel, U.; Mortensen, A.; Lam, H. R.; Larsen, E. H. (Part. Fibre Toxicol., 2011)

(untitled) - Sabella, S.; Carney, R. P.; Brunetti, V.; Malvindi, M. V.; Al-Juffali, N.; Vecchio, G.; Janes, S. M.; Bakr, O. M.; Cingolani, R.; Stellacci, F.; Pompa, P. P. (Nanoscale, 2014)

(untitled) - Vinković Vrček, I.; Pavičić, I.; Crnković, T.; Jurašin, D.; Babič, M.; Horák, D.; Lovrić, M.; Ferhatović, L.; Ćurlin, M.; Gajović, S. (RSC Adv., 2015)

(untitled) - Barbir, R.; Goessler, W.; Ćurlin, M.; Micek, V.; Milić, M.; Vuković, B.; Milić, M.; Ljubojević, M.; Domazet Jurašin, D.; Vinković Vrček, I. (Part. Part. Syst. Charact., 2019)

(untitled) - Kubo, A.-L.; Capjak, I.; Vrček, I. V.; Bondarenko, O. M.; Kurvet, I.; Vija, H.; Ivask, A.; Kasemets, K.; Kahru, A. (Colloids Surf., B, 2018)

(untitled) - Jacobs, C.; Müller, R. H. (Pharm. Res., 2002)

(untitled) - Prucek, R.; Panáček, A.; Fargašová, A.; Ranc, V.; Mašek, V.; Kvítek, L.; Zbořil, R. (CrystEngComm, 2011)

(untitled) - Im, S. H.; Lee, Y. T.; Wiley, B.; Xia, Y. (Angew. Chem., Int. Ed., 2005)

(untitled) - Yang, J.; Zhang, Q.; Lee, J. Y.; Too, H.-P. (J. Colloid Interface Sci., 2007)

(untitled) - Henglein, A.; Linnert, T.; Mulvaney, P. (Ber. Bunsen-Ges., 1990)

(untitled) - El Badawy, A. M.; Luxton, T. P.; Silva, R. G.; Scheckel, K. G.; Suidan, M. T.; Tolaymat, T. M. (Environ. Sci. Technol., 2010)

(untitled) - Capjak, I.; Goreta, S. Š.; Jurašin, D. D.; Vrček, I. V. (Arh. Hig. Rada Toksikol., 2017)

(untitled) - Docter, D.; Westmeier, D.; Markiewicz, M.; Stolte, S.; Knauer, S. K.; Stauber, R. H. (Chem. Soc. Rev., 2015)

(untitled) - Csapó, E.; Patakfalvi, R.; Hornok, V.; Tóth, L. T.; Sipos, Á.; Szalai, A.; Csete, M.; Dékány, I. (Colloids Surf., B, 2012)

(untitled) - Ravindran, A.; Dhas, S. P.; Chandrasekaran, N.; Mukherjee, A. (J. Exp. Nanosci., 2013)

(untitled) - Abdelkhaliq, A.; van der Zande, M.; Undas, A. K.; Peters, R. J. B.; Bouwmeester, H. (Nanotoxicology, 2020)

(untitled) - Klaus, T.; Joerger, R.; Olsson, E.; Granqvist, C.-G. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Phanjom, P.; Ahmed, G. (Nano Sci. Nano Technol., 2015)

Spectral Database for Organic Compounds SDBS - National Institute of Advanced Industrial Science and Technology

(untitled) - Pem, B.; Pongrac, I. M.; Ulm, L.; Pavičić, I.; Vrček, V.; Domazet Jurašin, D.; Ljubojević, M.; Krivohlavek, A.; Vinković Vrček, I. (Beilstein J. Nanotechnol., 2019)

(untitled) - Smith, A. M.; Marbella, L. E.; Johnston, K. A.; Hartmann, M. J.; Crawford, S. E.; Kozycz, L. M.; Seferos, D. S.; Millstone, J. E. (Anal. Chem. (Washington, DC, U. S.), 2015)

(untitled) - Liu, X.; Yu, M.; Kim, H.; Mameli, M.; Stellacci, F. (Nat. Commun., 2012)

(untitled) - López-Cebral, R.; Martín-Pastor, M.; Seijo, B.; Sanchez, A. (Prog. Nucl. Magn. Reson. Spectrosc., 2014)

(untitled) - Pem, B.; Toma, M.; Vrček, V.; Vinković Vrček, I. (Inorg. Chem., 2021)

(untitled) - De Matteis, V. (Toxics, 2017)

(untitled) - Stebounova, L. V.; Guio, E.; Grassian, V. H. (J. Nanopart. Res., 2011)